Adhesive Film

A multi-layer adhesive film with dendrite-like and nucleus-conductive particles addresses the reliability and conductivity issues in existing adhesive films, ensuring stable connections and performance across varying temperatures.

JP7663312B2Active Publication Date: 2025-04-16RESONAC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2018568551
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-02-17
Filing Date
2018-02-14
Publication Date
2025-04-16
Estimated Expiration
2038-02-14

AI Technical Summary

Technical Problem

Existing adhesive films used in electronic component applications lack sufficient reliability and conductivity to meet the demands of high-density and high-definition electronic components.

Method used

The adhesive film comprises a multi-layer structure with a first adhesive layer containing dendrite-like conductive particles and a second adhesive layer containing conductive particles with a non-conductive nucleus and a conductive layer, which together provide enhanced conductivity and reliability.

Benefits of technology

The multi-layer adhesive film achieves excellent reliability and conductivity, maintaining desired performance even with changes in ambient temperature, and allows for reduced content of conductive particles while ensuring stable connections between electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663312000003
    Figure 0007663312000003
  • Figure 0007663312000004
    Figure 0007663312000004
  • Figure 0007663312000005
    Figure 0007663312000005
Patent Text Reader

Abstract

One aspect of the present invention is an adhesive film comprising a first adhesive layer containing first conductive particles that are dendritic conductive particles, and a second adhesive layer containing second conductive particles that are conductive particles other than the first conductive particles and have a non-conductive core and a conductive layer provided on the core.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive film. [Background technology]

[0002] In recent years, various adhesives have been used in fields such as semiconductors and liquid crystal displays for fixing electronic components, connecting circuits, etc. In these applications, electronic components, circuits, etc. have become increasingly dense and precise, and adhesives are also required to have a higher level of performance.

[0003] For example, adhesives with conductive particles dispersed therein are used for connecting a liquid crystal display and a TCP (Tape Carrier Package), connecting an FPC (Flexible Printed Circuit) and a TCP, or connecting an FPC and a printed wiring board. Such adhesives are required to have even higher conductivity and reliability.

[0004] For example, Patent Document 1 describes a conductive film having a conductive layer containing predetermined dendritic silver-coated copper powder particles on a base film, and discloses that such a conductive film can provide sufficient conductive properties even without the incorporation of silver powder. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2014 / 021037 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an adhesive film having excellent reliability. [Means for solving the problem]

[0007] One aspect of the present invention is an adhesive film comprising a first adhesive layer containing first conductive particles which are dendritic conductive particles, and a second adhesive layer containing second conductive particles which are conductive particles other than the first conductive particles and have a non-conductive core and a conductive layer provided on the core.

[0008] The first adhesive layer may further contain second conductive particles. In this case, the volume ratio of the second conductive particles in the first adhesive layer may be smaller than the volume ratio of the second conductive particles in the second adhesive layer. The first adhesive layer may not contain the second conductive particles.

[0009] In another aspect, the adhesive film may be an adhesive film comprising, in this order, the first adhesive layer, the second adhesive layer, and a third adhesive layer, wherein the third adhesive layer contains third conductive particles which are dendritic conductive particles.

[0010] The third adhesive layer may further contain second conductive particles. In this case, the volume ratio of the second conductive particles in the third adhesive layer may be smaller than the volume ratio of the second conductive particles in the second adhesive layer. The third adhesive layer may not contain the second conductive particles.

[0011] The conductive layer may contain at least one selected from the group consisting of gold, nickel, and palladium. Effect of the Invention

[0012] According to the present invention, it is possible to provide an adhesive film with excellent reliability. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic cross-sectional view showing one embodiment of an adhesive film. [Diagram 2] FIG. 2 is a cross-sectional view of a main portion that illustrates an example of a connection between electronic members. [Diagram 3] FIG. 4 is a schematic cross-sectional view showing another embodiment of the adhesive film. [Figure 4] FIG. 11 is a cross-sectional view of a main portion that illustrates another example of a connection between electronic members. [Diagram 5] 1A to 1C are schematic diagrams showing a method for producing a mounting body for a reliability test. [Figure 6] FIG. 2 is a schematic diagram showing a method for measuring a connection resistance in a reliability test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.

[0015] Fig. 1 is a schematic cross-sectional view showing one embodiment (first embodiment) of an adhesive film. As shown in Fig. 1, an adhesive film 1A according to the first embodiment includes a first adhesive layer 2 and a second adhesive layer 3 provided on one surface of the first adhesive layer 2. The first adhesive layer 2 contains a first adhesive component 4 and first conductive particles 5 dispersed in the first adhesive component 4. The second adhesive layer 3 contains a second adhesive component 6 and second conductive particles 7 dispersed in the second adhesive component 6.

[0016] The first adhesive component 4 and the second adhesive component 6 may be the same or different from each other, and are preferably the same from the viewpoint of obtaining a stable adhesive strength against changes in environmental temperature. The first adhesive component 4 and the second adhesive component 6 may each be an adhesive component described below.

[0017] The adhesive component is composed of a material that exhibits curing properties due to heat or light, and may be, for example, an epoxy adhesive, a radical curing adhesive, or a thermoplastic adhesive such as polyurethane or polyvinyl ester. The adhesive component may be composed of a crosslinkable material because it has excellent heat resistance and moisture resistance after adhesion. Among these, an epoxy adhesive containing an epoxy resin, which is a thermosetting resin, as a main component is preferably used because it can be cured in a short time, has good connection workability, and has excellent adhesive properties. A radical curing adhesive has characteristics such as excellent curing properties at low temperatures and in a short time compared to an epoxy adhesive, and is used appropriately depending on the application.

[0018] The epoxy-based adhesive contains, for example, a thermosetting material such as an epoxy resin and a curing agent, and may further contain a thermoplastic resin, a coupling agent, a filler, and the like, as necessary.

[0019] Examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, bisphenol F novolac type epoxy resins, alicyclic epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, hydantoin type epoxy resins, isocyanurate type epoxy resins, and aliphatic chain epoxy resins. These epoxy resins may be halogenated or hydrogenated, and may have a structure in which an acryloyl group or a methacryloyl group is added to a side chain. These epoxy resins may be used alone or in combination of two or more.

[0020] The curing agent is not particularly limited as long as it can cure the epoxy resin, and examples thereof include anionic polymerization catalyst-type curing agents, cationic polymerization catalyst-type curing agents, polyaddition-type curing agents, etc. The curing agent is preferably anionic or cationic polymerization catalyst-type curing agents, since they are excellent in fast curing properties and do not require consideration of chemical equivalents.

[0021] Examples of the anionically or cationic polymerizable catalyst-type curing agent include imidazoles, hydrazides, boron trifluoride-amine complexes, onium salts (aromatic sulfonium salts, aromatic diazonium salts, aliphatic sulfonium salts, etc.), aminimides, diaminomaleonitrile, melamine and its derivatives, polyamine salts, dicyandiamide, etc., and may be modified products thereof. Examples of the polyaddition-type curing agent include polyamines, polymercaptans, polyphenols, acid anhydrides, etc.

[0022] These latent curing agents are preferably microencapsulated by coating them with a polymeric substance such as polyurethane or polyester, a thin metal film such as nickel or copper, or an inorganic substance such as calcium silicate, because the pot life can be extended. The curing agents are used alone or in combination of two or more.

[0023] The content of the curing agent may be 0.05 to 20 parts by mass per 100 parts by mass of the total amount of the thermosetting material and the thermoplastic resin that is blended as necessary.

[0024] The radical curing adhesive contains, for example, a radical polymerizable material and a radical polymerization initiator (also called a curing agent), and may further contain a thermoplastic resin, a coupling agent, a filler, etc., as necessary.

[0025] The radical polymerizable material may be any material having a functional group that is polymerized by a radical, without any particular limitations. Specifically, the radical polymerizable material may be, for example, an acrylate (including the corresponding methacrylate; the same applies below) compound, an acryloxy (including the corresponding methacryloxy; the same applies below) compound, a maleimide compound, a citraconic imide resin, a nadiimide resin, or the like. These radical polymerizable materials may be in the form of a monomer or an oligomer, or may be in the form of a mixture of a monomer and an oligomer.

[0026] Examples of the acrylate compound include methyl acrylate, ethyl acrylate, isopropyl acrylate, isobutyl acrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, trimethylolpropane triacrylate, tetramethylolmethane tetraacrylate, 2-hydroxy-1,3-diacryloxypropane, 2,2-bis[4-(acryloxymethoxy)phenyl]propane, 2,2-bis[4-(acryloxypolyethoxy)phenyl]propane, dicyclopentenyl acrylate, tricyclodecanyl acrylate, tris(acryloyloxyethyl)isocyanurate, urethane acrylate, and phosphate diacrylate.

[0027] The radical polymerizable substance such as an acrylate compound may be used together with a polymerization inhibitor such as hydroquinone or methyl ether hydroquinone, if necessary. From the viewpoint of improving heat resistance, the radical polymerizable substance such as an acrylate compound preferably has at least one substituent such as a dicyclopentenyl group, a tricyclodecanyl group, or a triazine ring. As the radical polymerizable substance other than the acrylate compound, for example, the compounds described in International Publication No. 2009 / 063827 can be suitably used. The radical polymerizable substance is used alone or in combination of two or more kinds.

[0028] The radical polymerization initiator can be any compound that generates free radicals by decomposing under heating or light irradiation. Specifically, the radical polymerization initiator may be, for example, a peroxide compound, an azo compound, or the like. These compounds are appropriately selected depending on the intended connection temperature, connection time, pot life, and the like.

[0029] More specifically, the radical polymerization initiator preferably includes diacyl peroxide, peroxydicarbonate, peroxy ester, peroxy ketal, dialkyl peroxide, hydroperoxide, silyl peroxide, etc. Among these, peroxy ester, dialkyl peroxide, hydroperoxide, silyl peroxide, etc. are preferred, and peroxy ester is more preferred from the viewpoint of obtaining high reactivity. As these radical polymerization initiators, for example, compounds described in International Publication No. 2009 / 063827 can be suitably used. The radical polymerization initiator is used alone or in combination of two or more kinds.

[0030] The content of the radical polymerization initiator may be 0.1 to 10 parts by mass relative to 100 parts by mass of the total amount of the radically polymerizable material and the thermoplastic resin that is blended as necessary.

[0031] Thermoplastic resins, which are optionally blended in epoxy adhesives and radical curing adhesives, can, for example, easily impart excellent film formability to the adhesive. Examples of thermoplastic resins include phenoxy resins, polyvinyl formal resins, polystyrene resins, polyvinyl butyral resins, polyester resins, polyamide resins, xylene resins, polyurethane resins, polyester urethane resins, phenol resins, and terpene phenol resins. Examples of thermoplastic resins that can be suitably used include compounds described in International Publication No. 2009 / 063827. The thermoplastic resin is preferably a phenoxy resin, since it is excellent in adhesion, compatibility, heat resistance, mechanical strength, and the like. The thermoplastic resins are used alone or in combination of two or more.

[0032] The content of the thermoplastic resin may be 5 to 80 parts by mass relative to 100 parts by mass of the total amount of the thermoplastic resin and the thermosetting material when blended into an epoxy adhesive. The content of the thermoplastic resin may be 5 to 80 parts by mass relative to 100 parts by mass of the total amount of the thermoplastic resin and the radically curable adhesive when blended into a radically curable adhesive.

[0033] Another example of the adhesive component is a thermal radical curing adhesive containing a thermoplastic resin, a radical polymerizable material containing a radical polymerizable substance that is liquid at 30°C, and a radical polymerization initiator. The thermal radical curing adhesive has a lower viscosity than the above-mentioned adhesive components. The content of the radical polymerizable substance in the thermal radical curing adhesive is preferably 20 to 80 parts by mass, more preferably 30 to 80 parts by mass, and even more preferably 40 to 80 parts by mass, relative to 100 parts by mass of the total amount of the thermoplastic resin and the radical polymerizable substance.

[0034] The adhesive component may be an epoxy adhesive containing a thermoplastic resin, a thermosetting material containing an epoxy resin that is liquid at 30° C., and a curing agent. In this case, the content of the epoxy resin in the epoxy adhesive is preferably 20 to 80 parts by mass, more preferably 40 to 80 parts by mass, and even more preferably 30 to 80 parts by mass, relative to 100 parts by mass of the total amount of the thermoplastic resin and the thermosetting material.

[0035] When the adhesive film 1A is used to connect an IC chip to a glass substrate, a flexible printed circuit board (FPC), or the like, the adhesive composition preferably further contains a component that exerts an internal stress relaxation effect in order to suppress warping of the substrate caused by the difference in linear expansion coefficient between the IC chip and the substrate. Specific examples of such components include acrylic rubber and elastomer components. Alternatively, the adhesive composition may be a radical curing adhesive as described in WO 98 / 44067.

[0036] The content of the first adhesive component 4 in the first adhesive layer 2 (the volume ratio of the first adhesive component 4 in the first adhesive layer 2) may be 75 mass% or more or 85 volume% or more, based on the total volume of the first adhesive layer 2, and may be 98 volume% or less or 92 volume% or less.

[0037] The content of the second adhesive component 6 in the second adhesive layer 3 (the volume ratio of the second adhesive component 6 in the second adhesive layer 3) may be 80 mass% or more or 90 mass% or more, based on the total volume of the second adhesive layer 3, and may be 98 volume% or less or 95 volume% or less.

[0038] The first adhesive layer 2 contains first conductive particles 5. The first conductive particles 5 are dendritic (also called dendritic) and have one main axis and a plurality of branches branching out from the main axis two-dimensionally or three-dimensionally. The first conductive particles 5 may be made of a metal such as copper or silver, and may be, for example, silver-coated copper particles obtained by coating copper particles with silver.

[0039] The first conductive particles 5 may be known particles, specifically, for example, available as ACBY-2 (Mitsui Mining & Smelting Co., Ltd.) or CE-1110 (Fukuda Metal Foil & Powder Co., Ltd.). Alternatively, the first conductive particles 5 can be produced by a known method (for example, the method described in the above-mentioned Patent Document 1).

[0040] The content of the first conductive particles 5 in the first adhesive layer 2 (the volume ratio of the first conductive particles 5 in the first adhesive layer 2) may be 2 volume % or more or 8 volume % or more, based on the total volume of the first adhesive layer 2, and may be 25 volume % or less or 15 volume % or less.

[0041] The thickness of the first adhesive layer 2 may be, for example, 5 μm or more, 7 μm or more, or 10 μm or more, and may be 30 μm or less, 25 μm or less, or 20 μm or less.

[0042] The second adhesive layer 3 contains second conductive particles 7 which are conductive particles other than the first conductive particles 5. The second conductive particles 7 have a non-conductive core and a conductive layer provided on the core. The core is made of a non-conductive material such as glass, ceramic, or resin, and is preferably made of resin. Examples of resins include acrylic resin, styrene resin, silicone resin, polybutadiene resin, and copolymers of monomers constituting these resins. The average particle size of the core may be, for example, 2 to 30 μm.

[0043] The conductive layer is formed of, for example, gold, silver, copper, nickel, palladium, or an alloy thereof. From the viewpoint of excellent conductivity, the conductive layer preferably contains at least one selected from gold, nickel, and palladium, more preferably contains gold or palladium, and further preferably contains gold. The conductive layer is formed, for example, by plating the core with the above metal. The thickness of the conductive layer may be, for example, 10 to 400 nm.

[0044] From the viewpoint of suitably reducing the thickness of the adhesive film 1A, the average particle size of the second conductive particles 7 is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less. The average particle size of the second conductive particles 7 may be, for example, 1 μm or more. The average particle size of the second conductive particles 7 is measured by a particle size distribution measuring device (Microtrac (product name, Nikkiso Co., Ltd.)) using a laser diffraction / scattering method.

[0045] The content of the second conductive particles 7 in the second adhesive layer 3 (the volume ratio of the second conductive particles 7 in the second adhesive layer 3) may be 2 volume % or more or 5 volume % or more, based on the total volume of the second adhesive layer 3, and may be 20 volume % or less or 10 volume % or less.

[0046] The thickness of the second adhesive layer 3 may be, for example, 5 μm or more, 7 μm or more, or 10 μm or more, and may be 30 μm or less, 25 μm or less, or 20 μm or less.

[0047] In the first embodiment, the first adhesive layer 2 contains only first conductive particles 5 as conductive particles, and the second adhesive layer 3 contains only second conductive particles 7 as conductive particles, but the first adhesive layer may further contain other conductive particles such as the second conductive particles 7, and the second adhesive layer may further contain other conductive particles such as the first conductive particles 5.

[0048] When the first adhesive layer further contains second conductive particles 7, the volume ratio of the second conductive particles 7 in the first adhesive layer is preferably smaller than the volume ratio of the second conductive particles 7 in the second adhesive layer, from the viewpoint of obtaining an adhesive film with even better reliability. The content of the second conductive particles 7 in the first adhesive layer may be, for example, 10 volume % or less, 5 volume % or less, or 2 volume % or less, based on the total volume of the first adhesive layer. From the same viewpoint, the first adhesive layer preferably does not contain the second conductive particles 7, as in the first embodiment.

[0049] The adhesive film 1A can be obtained, for example, by forming a first adhesive layer 2 and a second adhesive layer 3 separately and then laminating them. The first adhesive layer 2 and the second adhesive layer 3 can be obtained, for example, by applying a paste-like adhesive composition onto a resin film such as a PET (polyethylene terephthalate) film and drying it. The paste-like adhesive composition can be obtained, for example, by heating or dissolving in a solvent a mixture containing the adhesive components 4, 6 and the first conductive particles 5 or the second conductive particles 7. As the solvent, for example, a solvent having a boiling point of 50 to 150°C at normal pressure is used.

[0050] The adhesive film 1A according to the first embodiment can be used as an adhesive for bonding adherends of the same kind together, and can also be used as an adhesive for bonding adherends of different kinds (e.g., adherends having different thermal expansion coefficients) together. The adhesive film 1A is preferably used for connecting electronic components together.

[0051] Fig. 2 is a cross-sectional view of a main part showing an example of a connection between electronic components. First, as shown in Fig. 2(a), an adhesive film 1A is disposed between a first electronic component 10 including a first substrate 8 and a first electrode 9 formed, for example, over substantially the entire surface of the main surface of the first substrate 8, and a second electronic component 13 including a second substrate 11 and a second electrode 12 formed, for example, over substantially the entire surface of the main surface of the second substrate 11, to form a laminate 14A.

[0052] Next, the laminate 14A is heated and pressed in the direction indicated by the arrow A in Fig. 2(a) to electrically connect the first electronic member 10 and the second electronic member 13 to each other via the circuit connecting material 15A, as shown in Fig. 2(b), to obtain a connection structure 16A. The heating temperature is, for example, 50 to 190°C. The pressure during pressing is, for example, 0.1 to 30 MPa. The heating and pressing are performed for, for example, 0.5 to 120 seconds.

[0053] The first substrate 8 and the second substrate 11 may each be a substrate made of glass, ceramic, polyimide, polycarbonate, polyester, polyethersulfone, etc. The first electrode 9 and the second electrode 12 may each be an electrode made of gold, silver, copper, tin, aluminum, ruthenium, rhodium, palladium, osmium, iridium, platinum, indium tin oxide (ITO), etc.

[0054] The circuit connecting material 15A contains first conductive particles 5, second conductive particles 7, and a cured product 17A of the adhesive components 4 and 6. In other words, the circuit connecting material 15 is obtained by curing the above-mentioned adhesive film 1A.

[0055] The adhesive film 1A according to the first embodiment can suitably connect the electronic components 10, 13 together even when the first electrode 9 is made of a material (e.g., copper, aluminum) that is prone to forming an oxide film on its surface. This is believed to be due to the combined use of the first conductive particles 5 and the second conductive particles 7 in the adhesive film 1A. That is, as shown in FIG. 2(b), the second conductive particles 7 form a main conductive path that connects the first electrode 9 and the second electrode 12 to each other, while the first conductive particles 5 assist the electrical connection between the second conductive particles 7 and the first electrode 9, thereby achieving a suitable connection.

[0056] More specifically, the present inventors speculate that because the first conductive particles 5 are dendritic conductive particles, even if an oxide film is formed on the surface of the first electrode 9, the first conductive particles 5 can penetrate the oxide film and contact the first electrode 9, thereby enabling a suitable connection between the second conductive particles 7 and the first electrode 9. Therefore, it is considered that the adhesive film 1A according to the first embodiment is more reliable than an adhesive film using only either the first conductive particles or the second conductive particles, that is, it can maintain the desired conductivity against changes in environmental temperature.

[0057] Furthermore, the adhesive film 1A according to the first embodiment includes the first adhesive layer 2 containing the first conductive particles 5 and the second adhesive layer 3 containing the second conductive particles 7, which allows the electronic components 10, 13 to be connected together more suitably. Specifically, when connecting the electronic components 10, 13 together, the first adhesive layer 2 containing the first conductive particles 5 is adhered to the first electrode 9 of the first electronic component 10, so that the first conductive particles 5 in the first adhesive layer 2 come into contact with the first electrode 9, and in this state, the second conductive particles 7 in the second adhesive layer 3 come into contact with the first conductive particles 5. As a result, even if an oxide film is formed on the surface of the first electrode 9, the first conductive particles 5 can be more firmly in contact with the first electrode 9, which is believed to achieve a more stable connection.

[0058] Therefore, the adhesive film 1A according to the first embodiment is considered to have further improved reliability compared to, for example, an adhesive film consisting of a single layer containing both the first conductive particles 5 and the second conductive particles 7. Furthermore, the adhesive film 1A according to the first embodiment also makes it possible to reduce the content of the first conductive particles 5, while ensuring a suitable connection between the electronic components 10, 13, compared to, for example, an adhesive film consisting of a single layer containing both the first conductive particles 5 and the second conductive particles 7.

[0059] In another embodiment, the adhesive film may further include a third adhesive layer. FIG. 3 is a schematic cross-sectional view showing another embodiment (second embodiment) of the adhesive film. As shown in FIG. 3, the adhesive film 1B according to the second embodiment includes a first adhesive layer 2, a second adhesive layer 3, and a third adhesive layer 18 in this order. The first adhesive layer 2 contains a first adhesive component 4 and first conductive particles 5 dispersed in the first adhesive component 4. The second adhesive layer 3 contains a second adhesive component 6 and second conductive particles 7 dispersed in the second adhesive component 6. The third adhesive layer 18 contains a third adhesive component 19 and third conductive particles 20 dispersed in the third adhesive component 19.

[0060] The first adhesive component 4, the second adhesive component 6 and the third adhesive component 19 may be the same or different from each other, and are preferably the same from the viewpoint of obtaining a stable adhesive strength against changes in environmental temperature. The third adhesive component 19 may be the adhesive component described above.

[0061] The content of the third adhesive component 19 in the third adhesive layer 18 (the volume proportion of the third adhesive component 19 in the third adhesive layer 18) may be 75 volume % or more or 85 volume % or more, and may be 98 volume % or less or 92 volume % or less, based on the total volume of the third adhesive layer 18.

[0062] The third adhesive layer 18 contains third conductive particles 20 which are dendritic conductive particles. Details of the third conductive particles 20 are the same as those of the first conductive particles 5 described above, and a duplicated description will be omitted here. The third conductive particles 20 may be the same type as the first conductive particles 5 or may be different from them, and are preferably the same type from the viewpoint of obtaining a stable adhesive force against changes in environmental temperature.

[0063] The content of the third conductive particles 20 in the third adhesive layer 18 (the volume ratio of the third conductive particles 20 in the third adhesive layer 18) may be 2 volume % or more or 8 volume % or more, and may be 25 volume % or less or 15 volume % or less, based on the total volume of the third adhesive layer 18.

[0064] The thickness of the third adhesive layer 18 may be, for example, 5 μm or more, 7 μm or more, or 10 μm or more, and may be 30 μm or less, 25 μm or less, or 20 μm or less.

[0065] In the second embodiment, the third adhesive layer 18 contains only the third conductive particles 20 as the conductive particles, but the third adhesive layer may further contain other conductive particles such as the second conductive particles 7.

[0066] When the third adhesive layer further contains the second conductive particles 7, the volume ratio of the second conductive particles 7 in the third adhesive layer is preferably smaller than the volume ratio of the second conductive particles 7 in the second adhesive layer, from the viewpoint of obtaining an adhesive film with even better reliability. The content of the second conductive particles 7 in the third adhesive layer may be, for example, 10 volume % or less, 5 volume % or less, or 2 volume % or less, based on the total volume of the third adhesive layer. From the same viewpoint, the third adhesive layer preferably does not contain the second conductive particles 7, as in the second embodiment.

[0067] The adhesive film 1B according to the second embodiment can be obtained, for example, by separately forming the first adhesive layer 2, the second adhesive layer 3, and the third adhesive layer 18, and then laminating them together. The third adhesive layer 18 can be obtained by a method similar to the method for forming the first adhesive layer 2 and the second adhesive layer 3 described above.

[0068] The adhesive film 1B of the second embodiment can also be used as an adhesive for bonding adherends of the same type together, and can also be used as an adhesive for bonding adherends of different types (e.g., adherends having different thermal expansion coefficients) together, and is further suitable for use in connecting electronic components together.

[0069] Fig. 4 is a cross-sectional view of a main part, which shows a schematic diagram of another example of the connection between electronic components. Hereinafter, explanations that overlap with the example of the connection between electronic components shown in Fig. 2 will be omitted. In this example, as shown in Fig. 4(a), an adhesive film 1B according to the second embodiment is disposed between a first electronic component 10 and a second electronic component 13 to form a laminate 14B.

[0070] Next, in the same manner as described above, the laminate 14B is heated and pressed in the direction indicated by the arrow A in Fig. 4(a), so that the first electronic member 10 and the second electronic member 13 are electrically connected to each other via the circuit connecting material 15B, as shown in Fig. 4(b), to obtain a connection structure 16B. The circuit connecting material 15B contains the first conductive particles 5, the second conductive particles 7, the third conductive particles 20, and a cured product 17B of the adhesive component. That is, the circuit connecting material 15B is obtained by curing the above-mentioned adhesive film 1B.

[0071] The adhesive film 1B according to the second embodiment can suitably connect the electronic components 10 and 13 together even when the second electrode 12 is made of a material (e.g., copper or aluminum) that is likely to form an oxide film on its surface in addition to the first electrode 9. This is because the third conductive particles 20 are dendritic conductive particles, and therefore even when an oxide film is formed on the surface of the second electrode 12, the third conductive particles 20 can penetrate the oxide film and contact the second electrode 12. Therefore, the adhesive film 1B according to the second embodiment is more reliable than an adhesive film using only either the first conductive particles or the second conductive particles, i.e., it is considered that the adhesive film 1B according to the second embodiment can maintain the desired conductivity against changes in environmental temperature.

[0072] Furthermore, the adhesive film 1B according to the second embodiment includes the first adhesive layer 2 containing the first conductive particles 5, the second adhesive layer 3 containing the second conductive particles 7, and the third adhesive layer 18 containing the third conductive particles 20, in this order, which makes it possible to more suitably connect the electronic components 10 and 13 to each other. Specifically, even if an oxide film is formed on the surface of the second electrode 12 in addition to the first electrode 9, when connecting the electronic components 10 and 13 to each other, the first conductive particles 5 in the first adhesive layer 2 can be brought into contact with the first electrode 9 in preference to the second conductive particles 7 in the second adhesive layer 3, and the third conductive particles 20 in the third adhesive layer 18 can be brought into contact with the second electrode 12 in preference to the second conductive particles 7 in the second adhesive layer 3.

[0073] Therefore, the adhesive film 1B according to the second embodiment is considered to have further improved reliability compared to, for example, an adhesive film consisting of a single layer containing the first conductive particles 5 (third conductive particles 20) and the second conductive particles 7. Furthermore, the adhesive film 1B according to the second embodiment also makes it possible to reduce the content of the first conductive particles 5 (third conductive particles 20) while ensuring a suitable connection between the electronic components 10, 13, compared to, for example, an adhesive film consisting of a single layer containing the first conductive particles 5 (third conductive particles 20) and the second conductive particles 7. EXAMPLES

[0074] The present invention will be described in more detail below based on examples, but the present invention is not limited to the following examples.

[0075] (Preparation of Solution A1) 50 g of phenoxy resin (manufactured by Union Carbide Corporation, product name: PKHC, weight average molecular weight: 45000) was dissolved in a mixed solvent (mass ratio of toluene:ethyl acetate = 1:1) of toluene (boiling point: 110.6 ° C) and ethyl acetate (boiling point: 77.1 ° C) to obtain a phenoxy resin solution with a solid content of 40 mass %. This phenoxy resin solution was mixed with urethane acrylate (manufactured by Negami Chemical Industry Co., Ltd., product name: UN7700) and phosphate ester dimethacrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name: Light Ester P-2M) as radical polymerizable substances, and 1,1-bis (t-hexylperoxy)-3,3,5-trimethylcyclohexane (manufactured by Nippon Oil & Fats Corporation, product name: Perhexa TMH) as a curing agent in a solid mass ratio of phenoxy resin:urethane acrylate:phosphate ester dimethacrylate:curing agent = 10:10:3:2 to obtain solution A1.

[0076] As the conductive particles B1 (first conductive particles), dendritic conductive particles (silver-coated copper particles, manufactured by Mitsui Mining & Smelting Co., Ltd., product name: ACBY-2) were used.

[0077] (Preparation of core (resin particles)) Benzoyl peroxide was added as a polymerization initiator to a mixed solution of divinylbenzene, styrene monomer, and butyl methacrylate, and the mixture was heated while being uniformly stirred at high speed to carry out a polymerization reaction, resulting in a fine particle dispersion. This fine particle dispersion was filtered and dried under reduced pressure to obtain a block body, which is an aggregate of fine particles. Furthermore, this block body was pulverized to produce cores (resin particles) with an average particle diameter of 20 μm, each with a different crosslinking density.

[0078] (Preparation of conductive particles C1) A palladium catalyst (manufactured by Muromachi Technos Co., Ltd., product name: MK-2605) was supported on the surface of the core, and the core was activated using an accelerator (manufactured by Muromachi Technos Co., Ltd., product name: MK-370). The core was put into a mixed solution of nickel sulfate aqueous solution, sodium hypophosphite aqueous solution, and sodium tartrate aqueous solution heated to 60°C, and an electroless plating pre-step was performed. The mixture was stirred for 20 minutes, and it was confirmed that the bubbling of hydrogen had stopped. Next, a mixed solution of nickel sulfate, sodium hypophosphite, sodium citrate, and a plating stabilizer was added, and the mixture was stirred until the pH was stabilized, and an electroless plating post-step was performed until the bubbling of hydrogen had stopped. Next, the plating solution was filtered, and the filtrate was washed with water and then dried in a vacuum dryer at 80°C to produce nickel-plated conductive particles C1 (second conductive particles).

[0079] [Example 1] <Formation of a film from the adhesive composition> A mixed solution was obtained by dispersing 45 parts by volume of conductive particles B1 in 100 parts by volume of solution A1. The mixed solution obtained was applied onto a fluororesin film having a thickness of 80 μm, and the solvent was removed by drying with hot air at 70° C. for 10 minutes to obtain a film-like adhesive composition (first adhesive layer) having a thickness of 10 μm formed on the fluororesin film.

[0080] Next, 5 parts by volume of conductive particles C1 were dispersed in 100 parts by volume of solution A1 to obtain a mixed solution. The obtained mixed solution was applied onto a fluororesin film having a thickness of 80 μm, and the solvent was removed by drying with hot air at 70° C. for 10 minutes to obtain an adhesive composition (second adhesive layer) on a film having a thickness of 20 μm formed on the fluororesin film. The first adhesive layer was laminated onto the second adhesive layer, and the fluororesin film was peeled off to obtain an adhesive film having a thickness of 30 μm.

[0081] [Example 2] The first adhesive layer and the second adhesive layer were prepared in the same manner as in Example 1. In addition, the same adhesive layer as the first adhesive layer was prepared as the third adhesive layer. In the same manner as in Example 1, the first adhesive layer was laminated on the second adhesive layer, the fluororesin film on the second adhesive layer was peeled off, and then the third adhesive layer was laminated on the surface of the second adhesive layer opposite to the first adhesive layer, and the fluororesin film was peeled off to obtain an adhesive film having a thickness of 40 μm.

[0082] [Comparative Example 1] A mixed solution was obtained by dispersing 15 parts by volume of conductive particles C1 in 100 parts by volume of solution A1. The mixed solution obtained was applied onto a fluororesin film having a thickness of 80 μm, and the solvent was removed by drying with hot air at 70° C. for 10 minutes to obtain a film-like adhesive composition having a thickness of 40 μm formed on the fluororesin film.

[0083] [Comparative Example 2] A mixed solution was obtained by dispersing 30 parts by volume of conductive particles C1 in 100 parts by volume of solution A1. The mixed solution obtained was applied onto a fluororesin film having a thickness of 80 μm, and the solvent was removed by drying with hot air at 70° C. for 10 minutes to obtain a film-like adhesive composition having a thickness of 40 μm formed on the fluororesin film.

[0084] [Reference example 1] A mixed solution was obtained by dispersing 45 parts by volume of conductive particles B1 and 15 parts by volume of conductive particles C1 in 100 parts by volume of solution A1. The mixed solution obtained was applied onto a fluororesin film having a thickness of 80 μm, and the solvent was removed by drying with hot air at 70° C. for 10 minutes to obtain a film-like adhesive composition having a thickness of 30 μm formed on the fluororesin film.

[0085] The reliability of each of the adhesive films (film-like adhesive compositions) obtained in the Examples, Comparative Examples, and Reference Examples when used as a circuit connecting material was evaluated by the reliability test shown below. The results are shown in Tables 1 and 2.

[0086] <Reliability test> As shown in Figures 5(a) and (b), the adhesive film 21 cut to 6 mm x 6 mm was placed approximately in the center of the copper foil 22 of 6 mm x 50 mm, and was attached by applying heat and pressure (50°C, 0.5 MPa, 2 seconds) using BD-07 manufactured by Ohashi Manufacturing Co., Ltd. Next, as shown in Figures 5(c) and (d), a 50 mm x 6 mm aluminum foil 23 was prepared and placed on the laminate of the copper foil 22 and the adhesive film 21 so as to cover the adhesive film 21, and heat and pressure (150°C, 0.5 MPa, 10 seconds) were applied using BD-07 manufactured by Ohashi Manufacturing Co., Ltd. to obtain a mounting body for reliability testing. An ammeter and a voltmeter were connected to the obtained assembly, as shown in Fig. 6, and the connection resistance (initial) was measured by the four-terminal method. In addition, using a TSA-43EL manufactured by Espec Corporation, a heat cycle test was performed on the assembly, in which the heat cycle of holding at -20°C for 30 minutes, heating to 100°C over 10 minutes, holding at 100°C for 30 minutes, and cooling to -20°C over 10 minutes was repeated 500 times, and then the connection resistance (after the heat cycle test) was measured in the same manner as above.

[0087] [Table 1]

[0088] [Table 2] [Explanation of symbols]

[0089] 1A, 1B...adhesive film, 2...first adhesive layer, 3...second adhesive layer, 5...first conductive particles, 7...second conductive particles, 18...third adhesive layer, 20...third conductive particles.

Claims

1. a first adhesive layer containing first conductive particles which are dendritic conductive particles; a second adhesive layer containing second conductive particles, which are conductive particles other than the first conductive particles and have a non-conductive core and a conductive layer provided on the core; the first conductive particle is composed of only one main axis and a plurality of branches branching two-dimensionally or three-dimensionally from the main axis, the first conductive particles are conductive particles that are hardenable by heat or light in the first adhesive layer and are dispersed in a first adhesive component that contains a thermoplastic resin; the second conductive particles are conductive particles dispersed in a second adhesive component in the second adhesive layer, the second adhesive component is a thermal radical curing adhesive, The content of the radical polymerizable substance in the thermal radical curing adhesive is 20 to 80 parts by mass per 100 parts by mass of the total amount of the thermoplastic resin and the radical polymerizable substance, An adhesive film, wherein one of the radical polymerizable substances is a urethane acrylate.

2. the first adhesive layer further contains the second conductive particles; The adhesive film of claim 1 , wherein a volume percentage of the second conductive particles in the first adhesive layer is smaller than a volume percentage of the second conductive particles in the second adhesive layer.

3. The adhesive film of claim 1 , wherein the first adhesive layer does not contain the second conductive particles.

4. The adhesive tape includes, in this order, the first adhesive layer, the second adhesive layer, and a third adhesive layer; The adhesive film of any one of claims 1 to 3, wherein the third adhesive layer contains third conductive particles that are dendritic conductive particles.

5. the third adhesive layer further contains the second conductive particles; The adhesive film of claim 4 , wherein a volume percentage of the second conductive particles in the third adhesive layer is smaller than a volume percentage of the second conductive particles in the second adhesive layer.

6. The adhesive film of claim 4 , wherein the third adhesive layer does not contain the second conductive particles.

7. The adhesive film according to any one of claims 1 to 6, wherein the conductive layer contains at least one selected from the group consisting of gold, nickel and palladium.

Citation Information

Patent Citations

  • Connection member of circuit

    JP1989059786A

  • Conductive adhesive and method of mounting ic chip using the same

    JP2002324427A

  • Silvered copper powder

    JP2013100592A

  • Electroconductive film

    WO2014021037A1

  • Copper powder

    WO2015115139A1